A WR-2.8 band pseudoelliptic waveguide filter using TM110 and TE101 Dual-Mode cavities - Yao Chen; Yinian Feng (Materials & Design, 2025)
In this paper, a novel WR-2.8 band dual-mode filter with high selectivity and compact structure is proposed. The basic dual-mode cavity, by exciting and exploiting TM110 and TE101 modes, can provide two reflection zeros and one transmission zero (TZ). Also, the high design flexibility in terms of TZ position and filter bandwidth has been demonstrated. Due to the simple structure and good symmetry, the efficient mode-matching (MM) technique can be used for filter synthesis. For verification, the proposed pseudoelliptic filter is fabricated by high-precision computer numerical control (CNC) milling technology which the measured machining tolerance is less than ± 5 μm. The measured and simulated results of the proposed filter are all in a good agreement, which exhibits the lowest insertion loss of 0.75 dB, the return loss of better than 15 dB and the 3-dB bandwidth of 16 GHz centered at 292 GHz. Furthermore, high selectivity with two TZs located at 281 and 304 GHz is achieved.